Basal hormones and biochemical markers as predictors of overtraining syndrome in male athletes: The EROS-BASAL study - Cadegiani, F. A.; Kater, C. E. (2019)
Context: Overtraining syndrome (OTS) and related conditions cause decreased training performance and fatigue through an imbalance among training volume, nutrition, and recovery time. No definitive biochemical markers of OTS currently exist.